2002
DOI: 10.1093/humrep/17.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of evaluation of the uterus by transvaginal sonography, hysterosonographic examination, hysteroscopy and magnetic resonance imaging

Abstract: Inter-observer disagreement reached substantial levels only for exclusion of uterine cavity benign abnormalities by HY, TVS and HSE. Strategies should be adopted to reduce observer variation of common gynaecological imaging techniques or the less observer-dependent MRI technique could be favoured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 19 publications
3
43
2
1
Order By: Relevance
“…As suggested by Jurkovic,33 the storage of raw data may contribute to a more precise examination and consequently may result in high reliability, especially because the patient is no longer present and the data can be reviewed extensively. Our data support this view because the reproducibility of 3D-SIS is considerably better compared with a previous reliability analysis of SIS by Dueholm et al 34 They found a κ value for interobserver agreement of 0.48. It is well known that interpretation of SIS is more difficult if the endometrium is thick.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As suggested by Jurkovic,33 the storage of raw data may contribute to a more precise examination and consequently may result in high reliability, especially because the patient is no longer present and the data can be reviewed extensively. Our data support this view because the reproducibility of 3D-SIS is considerably better compared with a previous reliability analysis of SIS by Dueholm et al 34 They found a κ value for interobserver agreement of 0.48. It is well known that interpretation of SIS is more difficult if the endometrium is thick.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that interpretation of SIS is more difficult if the endometrium is thick. Although we are unaware of the timing of the cycle in the study by Dueholm et al, 34 we performed all SIS and 3D-SIS just after the bleeding had stopped. The interobserver agreement for SIS may increase if the procedure is performed strictly during the first days of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that both treatment arms reduced uterine volume and blood flow inside the uterus, a change that could have been the cause of the effect of the treatment. There is great variation in the ultrasound diagnostic accuracy of adenomyosis; we depended on this accuracy for the diagnosis of eligible participants [15].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, this is what we observed with the patient presented in this report: she experienced complete resolution of her urinary symptoms immediately after UAE, before significant reduction in fibroid or uterine mass occurred; the 14-cc shrinkage is most likely due to loss of blood flow to the previously plump vascular tumor. In the literature, Dueholm et al [7] evaluated perfusion and volume changes in relation to clinical outcome, obtaining MRI scans before, immediately following, and 1 and 4 months after UAE. They demonstrated that immediate reduction in enhancement at 90 seconds within the leiomyomata, indicating decreased perfusion, correlated with clinical response; however, that volume reduction did not.…”
Section: Discussionmentioning
confidence: 99%